(untitled) (Journal of Hama University, 2024)
The research was conducted at the Scientific Agricultural Research Center in Latakia (Stakhris Station) in (2022), where different levels of pressure applied to celty clay soil (0 , 163 , 216 , 297 kPa) were used, at three levels of humidity (20 , 24 , 28% by weighty) to determine the effect of pressure and humidity on the size of pores larger than 10 microns and on the saturated hydraulic conductivity coefficient with depth. The results showed the obvious and significant effect of soil compaction in the pore size greater than (10)microns and in the saturated hydraulic conductivity coefficient, in addition to the decrease in the value of the experimental constants by increasing the pressure, noting that the effect of pressure was decreasing with depth, as soil compaction in the surface layer (5 , 20 )cm led to a decrease in the saturated hydraulic conductivity coefficient to (1.11, 0.11)m/Day when applying pressures (163, 297)KPA as an average of moisture levels and moisture contributed to the pressure (297) KPA to decrease the coefficient of saturated hydraulic conductivity by( 0.10 )m/Day at a humidity of (28)% by weight.It was also noted that the air pores (larger than 10 microns) decreased with The increase in pressure and humidity during compression in the surface layer (5 , 20)cm, where the size of these pores when treated without pressure reached (20.39)% as an average relative to humidity and decreased significantly to (6.18)% at (297 )KPA, i.e. by (14.21)% exceeding the limit value (12%), where the size of these pores reached (3.44)% at( 297) KPA and humidity level (28)%, as the results showed the decrease was from (4521.59)cm2/plant in the treatment without pressure and moisture content (20%) to (2421.93 )cm2/plant at pressure (297 )kPa at the same moisture content.